ATD's 2020 trends in learning technology - Brusino, Justin (ATD Press, 2020)
Evolving Technology for Human Performance ATD's 2020 Trends in Learning Technology collects insights about the latest emerging tech and trends that are transforming the talent development profession from top experts. They give much food for thought about how talent development professionals should embrace, test, and adopt technology to advance their careers and organizations. These learning technologies may span a broad variety of opportunities and applications, but one thing unites them: the human element of how to apply the technologies to help people work better. While some will continue to evolve and find a place in your technology toolbox for years to come, others may never be embraced. No matter your role in talent development or the makeup of your organization, it is critical to regularly review new technologies and trends and evaluate if and how they fit into your organization. This book will help you stay in the know. Assembled here are chapters by seven people who like to experiment, tinker, create, play, and do. Each expert looks at a different trend, what effect it's had on the field, and what effect it may have in the future: microlearning by Shannon Tipton podcasting by Mike Lentz user experience design by Becca Wilson xAPI by Sean Putman and Sarah Mercier artificial intelligence by JD Dillon augmented and virtual reality by Destery Hildenbrand. Capping off the volume is a chapter on L & D's role in the changing, technology-driven business landscape by Brandon Carson. ATD's 2020 Trends in Learning Technology is your guide to the talent development landscape of tomorrow.